Cytokine Levels in the Preterm Infant with Neonatal Intestinal Injury - Bhatia, Amina M.; Stoll, Barbara J.; Cismowski, Mary J.; Hamrick, Shannon E. (American Journal of Perinatology, 2014)
Objectives The purpose of this study is to characterize the cytokine response of preterm newborns with surgical necrotizing enterocolitis (NEC) or spontaneous intestinal perforation (SIP) before surgical treatment and to relate these finding to intestinal disease (NEC vs. SIP).Study Design The study was a 14-month prospective, cohort study of neonates undergoing surgery or drainage for NEC or SIP or surgical ligation of patent ductus arteriosus (PDA). Multiplex cytokine detection technology was used to analyze six inflammatory markers: interleukin-2, interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-1 β (IL-1β), interferon-gamma, and tumor necrosis factor-α (TNF-α).Results Patients with NEC had much higher median preoperative levels of IL-6 (NEC: 8,381 pg/mL; SIP: 36 pg/mL; PDA: 25 pg/mL, p < 0.001), IL-8 (NEC: 18,438 pg/mL; SIP: 2,473 pg/mL; PDA: 1,110 pg/mL, p = 0.001), TNF-α (NEC: 161 pg/mL; SIP: 77 pg/mL; PDA: 71 pg/mL, p < 0.001), and IL-1β (NEC: 85 pg/mL; SIP: 31 pg/mL; PDA: 24 pg/mL, p = 0.001). Patients with NEC totalis (NEC-totalis had the highest levels of IL-8 and were significantly different from infants with limited NEC (28,141 vs. 11,429 pg/mL, p = 0.03).Conclusion Surgical NEC is a profoundly more proinflammatory disease than SIP. The cytokine profiles of patients with SIP are closer to those of a nonseptic surgical neonate.
Keywords: necrotizing enterocolitis; spontaneous intestinal perforation; cytokines; patent ductus arteriosus